THE IMPACTS OF EDUCATION ON SELF-MANAGEMENT OF ACUTE CORONARY SYNDROME PATIENTS WITH TYPE 2 DIABETES MELLITUS: LITERATURE REVIEW - Rini Ariani; Hema Malini; Dally Rahman (LLDIKTI Wilayah X, 2023)
Heart disease is the leading cause of death worldwide, about 32.2% of Acute Coronary Syndrome (ACS) patients reported also suffering from Diabetes Mellitus. ACS and DMT2 contribute greatly to the health status and quality of life of patients, thus requiring coordinated management and health education that can improve knowledge, self-efficacy, and self-management behaviors in ACS patients with DMT2. Research on education of ACS patients with T2DM is still limited, so the purpose of this literature review is to evaluate the benefits of education on self-management of ACS patients with T2DM. The databases used are Sciencedirect, Pubmed, Cochrane Library, and Proquest, articles published in the last 5 years. The main keyword combinations used are Acute Coronary Syndrome, Education, Self-Management, and Type 2 Diabetes Mellitus. The first search results found 451 articles, after screening and evaluation, 3 articles met the criteria. The results of the review showed that providing education during face-to-face treatment can improve fasting blood glucose, ACS symptom management, and DMT2 self-management. Education during treatment with 1-2 phone calls and social media affects the patient's ability to manage ACS symptoms at discharge. It also found the impact of continuous education on self-management delivered during follow-up, conducted via telephone, social media applications, and home visits. Thus, health workers are expected to be able to provide education to ACS and DMT2 patients face-to-face, telephone, social media, videos, and education continuously with home visits.